(3cJGH aj GdWHs - (3CHh GdMSf Ydj Hf CHj GdMQK GdbQTj GdeWHHs
(3ChdgG (B:s
(3bGd GdTjN GdNHjQ bOhI GdYdeGA GHh GdMSf Ydi GHf GdMQK GdbQTi GdeWHH gPG GdcJGH Ydi CQHYI afhf Gdaf GdChd ai bhGYO LRi GdWH GYfi Ydeg hYedg s
(3BNQgG (B:s
(3hGeG QjGM hGHNQI ai CYVGA GdfaS ef CMeJ cd jhe ddCfVGL s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdWHs